(untitled) (Revista Peruana de Investigación Educativa, 2011)
The article presents a diagnosis of the funding and budget management of the public education in Peru in a context of a political decentralization process that has implied the transfer of education competencies and functions to the sub national governments. Based on the analysis of the legal framework, budget information and evidence obtained through case studies, we identify key practices of the financing and transfers of resources to the regional and municipal governments, as well as the some of the main characteristics and results of budget allocation and execution processes at those government levels. This allows us to identify some important achievements and problems of the decentralized budgeting management of the educational sector.